2005
DOI: 10.1007/bf03347242
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin (OPG) and receptor activator of NF-kB ligand (RANK-L) serum levels in patients on chronic hemodialysis

Abstract: The mechanisms underlying the skeletal resistance to PTH in patients on chronic hemodialysis (CHD) are not yet fully clarified. Osteoprotegerin (OPG) and receptor activator of NF-kB ligand (RANK-L) modulate the genesis and activity of osteoclasts, however their role in renal osteodystrophy pathogenesis has not been clarified so far. The present study aimed to evaluate OPG and RANK-L serum levels in hemodialysis patients and whether OPG/RANK-L system could have a role in the skeletal resistance to PTH. In fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…OPG levels are significantly higher in patients with chronic kidney disease compared with age-and sex-matched controls, and increasing OPG levels have a linear relationship with worsening renal function (96). Similar findings are noted in patients with chronic kidney disease on hemodialysis (97). In the study by Nitta et al (98), 102 patients on regular hemodialysis were assessed for aortic calcification by a noncontrast computed tomography scan.…”
Section: Opg and Cardiovascular Disease In Chronic Kidney Diseasementioning
confidence: 68%
“…OPG levels are significantly higher in patients with chronic kidney disease compared with age-and sex-matched controls, and increasing OPG levels have a linear relationship with worsening renal function (96). Similar findings are noted in patients with chronic kidney disease on hemodialysis (97). In the study by Nitta et al (98), 102 patients on regular hemodialysis were assessed for aortic calcification by a noncontrast computed tomography scan.…”
Section: Opg and Cardiovascular Disease In Chronic Kidney Diseasementioning
confidence: 68%
“…The higher level expression of RANKL and cathepsin‐K in LFKO −/− I mice was associated with the active state of bone resorption compared to WTI mice. Additionally, the levels of OPG, which prevents the activation of NF‐κB, were inversely proportional to those of RANKL 7,47 . It has also been reported that higher levels of RANKL mRNA in experimental periodontitis lead to bone resorption 7 .…”
Section: Discussionmentioning
confidence: 90%
“…Serum levels of both OPG and RANKL are elevated in hemodialysis patients and have been investigated as potential biomarkers of CAD in patients with stage 4 and 5 CKD [2527]. Elevated serum OPG levels correlate with increased coronary artery calcification and mortality [8, 25, 26].…”
Section: Discussionmentioning
confidence: 99%